2008
DOI: 10.1136/vr.163.1.11
|View full text |Cite
|
Sign up to set email alerts
|

Detection of spinal cord compression in dogs with cervical intervertebral disc disease by magnetic resonance imaging

Abstract: The medical records and magnetic resonance images of 33 dogs with surgically confirmed Hansen type I cervical intervertebral disc disease were reviewed. Fourteen of the dogs were chondrodystrophic and 19 were not chondrodystrophic. The most common clinical sign was neck pain, which affected 28 of the dogs, and 23 of the dogs were able to walk. Fifteen of the dogs had developed clinical signs acutely, within the previous 24 hours. On cross-sectional images the median area of spinal cord compression was 26 per c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
56
1
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(66 citation statements)
references
References 14 publications
5
56
1
4
Order By: Relevance
“…One dog had 2 caudal lumbar region IVDEs. The T13-L1 IVDS was most often affected (n = 16), followed by T12-13 (14), L3-4 and L6-7 (11 each), L2-3 (8), L5-6 (7), L4-5 (5), T11-12 and L7-S1 (4 each), and T10-11 and L1-2 (1 each). In the dog with 2 concurrent IVDEs, the L6-7 and L7-S1 IVDSs were affected.…”
Section: English Cocker Spanielsmentioning
confidence: 99%
See 1 more Smart Citation
“…One dog had 2 caudal lumbar region IVDEs. The T13-L1 IVDS was most often affected (n = 16), followed by T12-13 (14), L3-4 and L6-7 (11 each), L2-3 (8), L5-6 (7), L4-5 (5), T11-12 and L7-S1 (4 each), and T10-11 and L1-2 (1 each). In the dog with 2 concurrent IVDEs, the L6-7 and L7-S1 IVDSs were affected.…”
Section: English Cocker Spanielsmentioning
confidence: 99%
“…3,4,[8][9][10][11][12] English Cocker Spaniels are also predisposed to IVDE, and this breed is among the 7 breeds at highest risk for this disorder. 2,5,6,13,14 Although anecdotal information suggests a higher incidence of lumbosacral IVDEs in English Cocker Spaniels than in other dog breeds, 15 little is known about characteristics of thoracolumbar and lumbar IVDE in this breed. Therefore, the purpose of the study reported here was to characterize the clinical signs and findings associated with IVDE of these regions in English Cocker Spaniels.…”
mentioning
confidence: 99%
“…In dogs, 83.6% of SCI is associated with IVDH, located in the thoracolumbar region between T10 and L7 [17]. Among all dogs with cervical disc herniation, the most commonly affected IVD spaces are represented at C5-C6 and C6-C7 [1819]. In nonhuman primates, the experimentally induced SCI model has been reported, but acute cervical SCI associated IVDH has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…15 Intervertebral disk protrusions affecting the cervical spinal cord may also produce ipsilateral Horner's syndrome as a result of disruption of the descending lateral tectotegmental spinal tract that controls the sympathetic LMNs located in the T1-3 spinal cord segments. [18][19][20] MRI is the imaging modality of choice, as it allows assessment of the spinal cord. Dysphonia or respiratory dysfunction can occur if edema and injury extends to the caudal brainstem or disrupts the descending respiratory pathways.…”
Section: Cervical Intervertebral Disk Diseasementioning
confidence: 99%